Estradiol-induced immune suppression via prostaglandin E2 during parturition in bovine leukemia virus-infected cattle. - Yamato Sajiki (PLoS ONE, 2022)
Immune suppression during pregnancy and parturition is considered a risk factor that is related to the progression of bovine chronic diseases, such as bovine leukosis, which is caused by bovine leukemia virus (BLV). Our previous studies have demonstrated that prostaglandin E2 (PGE2) suppresses BLV-specific Th1 responses and contributes to the disease progression during BLV infection. Although PGE2 reportedly plays important roles in the induction of parturition, PGE2 involvement in immune suppression during parturition is unknown. To investigate its involvement, we analyzed PGE2 kinetics and Th1 responses in BLV-infected pregnant cattle. PGE2 concentrations in sera were increased, whereas IFN-γ responses were decreased before delivery. PGE2 is known to suppress Th1 immune responses in cattle. Thus, these data suggest that PGE2 upregulation inhibits Th1 responses during parturition. We also found that estradiol was important for PGE2 induction in pregnant cattle. In vitro analyses indicated that estradiol suppressed IFN-γ production, at least in part, via PGE2/EP4 signaling. In vivo analyses showed that estradiol administration significantly influenced the induction of PGE2 production and impaired Th1 responses. Our data suggest that estradiol-induced PGE2 is involved in the suppression of Th1 responses during pregnancy and parturition in cattle, which could contribute to the progression of BLV infection.